Antimicrobial resistance and genomic characterization of Staphylococcus aureus in ready-to-eat foods from Mangaung Metro Municipality - Letuka, Pontso; Nkhebenyane, Sebolelo J.; Ramatla, Tsepo; Zikhona, Tywabi-Ngeva; Lekota, Kgaugelo E.; Khasapane, Ntelekwane G. (Frontiers in Microbiology, 2025)
Human staphylococcal food poisoning is caused by a range of heat-stable staphylococcal enterotoxins that are released into food by Staphylococcus aureus. Additionally, antimicrobial resistance has steadily grown into a significant global issue that endangers food safety and human health. Therefore, this study aimed to determine the frequency of S. aureus in foods sold on the streets of Mangaung Metropolitan Municipality, South Africa, and thoroughly examine the isolated strains’ genetic traits, virulence, and antibiotic resistance profiles. Out of 168 samples, which included salad, pap (maize meal), chicken, and pork, all (100%) samples showed the occurrence of Staphylococcus species. Furthermore, 29.7% of isolates were subsequently identified by MALDI-TOF MS as S. aureus. Moreover, antimicrobial susceptibility testing of 50 S. aureus isolates showed that 42% were resistant to penicillin, followed by cefoxitin at 46% and ciprofloxacin at 44%. The multidrug-resistant (MDR) profile revealed that 52% of the isolates were resistant to three or more classes of antibiotics. Additionally, four sequenced isolates were identified by in silico MLST as having sequence types (STs) 243, although strain SVF3 contained a unique ST designated as * ff2b. All four isolates were identified as belonging to Staphylococcal Protein A type (spa-type) t21 by whole genome sequencing. All sequenced isolates exhibited a total of 9 antibiotic resistance genes and 63 virulence genes. The current study showed the importance of monitoring for high virulence potential and antimicrobial resistance of S. aureus in retail food and increasing awareness of potential risk for such strains; furthermore, infection control measures, antimicrobial stewardship, and periodic One Health epidemiological surveillance studies are needed to monitor and contain the threat of increasing antibiotic resistance in Africa.